Bannayan–Riley–Ruvalcaba syndrome: a cause of extreme macrocephaly and neurodevelopmental delay. Issue 7 (25th March 2009) - Lynch, N E; Lynch, S A; McMenamin, J; Webb, D
Abstract : Background: Bannayan–Riley–Ruvalcaba syndrome (BRRS) is an autosomal dominant condition characterised by macrocephaly, developmental delay and subtle cutaneous features. BRRS results from mutations in the PTEN gene. In adults, PTEN mutations cause Cowden syndrome where, in addition to the macrocephaly, there is a higher risk of tumour development. Diagnosis of BRRS is often delayed as presentation can be variable, even within families. Aims: To identify characteristics of this condition which might facilitate early diagnosis. Prompt diagnosis not only avoids unnecessary investigations in the child but potentially identifies heterozygote parents who are at risk of tumour development. Methods and Results: Six children with a PTEN mutation were identified. All had extreme macrocephaly. Four parents and a male sibling were found to have a PTEN mutation on subsequent testing. Affected parents had extreme macrocephaly and a history of thyroid adenoma, or breast or skin lesions. All six children had presented to medical attention before the age of 2.5 years (3/6 were investigated as neonates), but the median age at diagnosis was 5 years. Four of the children had multiple investigations prior to identification of a PTEN mutation. Conclusion: BRRS should be considered in children with extreme macrocephaly as it is the most consistent clinical feature seen, particularly where there is a family history of macrocephaly.